Application of Single MEMS-accelerometer to Measure 3-axis Vibrations and 2-axis Tilt-Angle Simultaneously - Didik R. Santoso; Sukir Maryanto; Ahmad Nadhir (Universitas Ahmad Dahlan, 2015)
This paper discusses a technique of developing an integrated sensor system, to measure the mechanical vibrations in 3-axis and the tilt-angle in 2-axis simultaneously, using only single MEMS-accelerometer. Type of MEMS-accelerometer that used in this experiment is MMA7361L, which is an analog-type acceleration sensor in the form of MEMS, with a maximum sensitivity of 800 mV/g. The MMA7361L has three outputs of voltage (Vx, Vy, Vz) in response to the acceleration value